(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the socio-demographic profile and health-seeking behavior of under-five patients suffering from childhood pneumonia. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Frontier Medical & Dental College, Abbottabad, from June, 2014 to May, 2015, Materials and Methods: All under-five children suffering from acute respiratory tract infection were included in the study. They were diagnosed when there is a sudden onset of atleast one of cough, coryza, shortness of breath or sore throat within last seven days along-with a clinician’s diagnosis of infection. Patients with chronic respiratory illnesses were excluded from the study. Respondents were mothers or caretakers of sick children. A structured and pre-tested questionnaire was used to collect data. Questions were specifically asked about literacy and occupation, composition of household, history of respiratory tract infections in last one month, date of onset and duration of symptoms, distance to health facility and mode of transport used, type of treatment modality sought and the reason/s of choosing it. Results: Fifty three percent of patients were female while 74% were less than one year of age. Most of the caregivers were either uneducated (26.6%) or had education upto primary level (23.1%). Similarly, most of them of them were factory workers, 50.7%, and laborers, 21.8%, while only 20.1% were businessman. Most of the study participants, (97%), consulted health care provider for treatment of their child while 3% preferred self medication. Out of these, 76% consulted private facility, 21% visited public facility. There were various reasons for preferring different modes of treatment. Free medicines and lower consultation fee were the main reason for visiting dispensers and public health facility while modern health facilities and doctor’s reputation were the main reason for choosing private health facility. Conclusion: Many factors affect the health seeking attitude of caregivers of sick children. Income, occupation and education level of these caregivers play a pivotal role in choosing health care facility. Private health providers, despite being expensive, were preferred mode of treatment in our study. Government should improve public health services including emergency services. Other measures should include education of masses and increased budgetary allocations to health department which will help reduce the economic impact of childhood respiratory illnesses.